Assessing Landscape Perceptions of Urban Waterscapes - Sakici, Cigdem (Kamla Raj Enterprises, 2015)
Water is one of the most significant design elements that contributes to people feeling good physically, behaviorally and psychologically. This paper aims to reveal the landscape values of various ...
Keywords: 11. Sustainability; 3. Good health